Pemanfaatan Website Organisasi sebagai Media Keterbukaan Informasi Publik : Studi pada Website PSSI www.pssi.org - Prasetya, Narayana Mahendra (Jurnal Komunikator, 2015)
Based on The Law Number 14 Year 2008 about The Openness of Public Information (UU KIP), public organization in Indonesia must provide the public information as their duty for the public. Majority of research about practice of UU KIP discuss about the practice in government or state organization. Meanwhile, the public organization also include non-government organization. This article discuss about practice of the opennes of public information in Indonesian Football Association (PSSI). PSSI is one kind of non-government organization. PSSI also under the microscope because public thinks PSSI is not transparent related to their management. The focus of this article is how PSSI use their internet-based media to support theÂ practice of the opennes of public information. Theoritically, internet could support the organization in providing information to the public. There are four indicators to observe the internet usage: (1) transparency, (2) participation, (3) accountability, (4) effective and efficient. PSSI has did the transparency and accountability, but still non-ideal. Meanwhile for participation and effective and efficient, PSSI not doing it yet.Â Keywords: Indonesian Football Association, Internet, New Media, The Openness of Public Informmation, Website